PENGARUH MOTIVASI KERJA, BUDAYA KERJA DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI DINAS PERHUBUNGAN, KOMUNIKASI DAN INFORMATIKA KOTA PALU - Intan, Intan (Katalogis, 2017)
The Influence Of Work Motivation, Work Culture, And Communication On Officials’ Performance In The Department Of Transportation, Communication And Informatics Of Palu City. This research aims to determine and analyze simultaneous and partial influences of work motivation, work culture and communication on officials’ performance in the department of transportation, communication and informatics of Palu City. Sample consists of 66 officials in the office. Method of analysis is descriptive with multiple linear regressions. The results find that work motivation, work culture, and communication simultaneously have significant influence of officials’ performance in the department of transportation, communication and informatics of Palu City with Fcount of 21.618 on sig. 0,000. Motivation has significant infuence on officials’ performance with tcount 4.257 on sig 0,000; work culture has significant influence on officials’ performance with tcount 2,740 on sig 0,000; communication has significant influence on officials performance with tcount 3,210 on sig 0,000